The Influence of the Teacher's Role, Principal Leadership, and School Rules on Student Discipline in Middle Schools - Alam, M. Nurul; Fakhruddin, Fakhruddin; Raharjo, Tri Joko (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
School discipline is an effort that is consciously directed and organized to carry out the assigned tasks and can be accounted for according to their abilities; these efforts are realized to create school efficiency and achieve educational goals properly. This study aimed to determine the effect of teachers, principal leadership, and school discipline on student discipline. The research method used was quantitative. The subjects of this study were 8th & 9th-grade students of SMP Takhassus Al-Qur'an Sunan Gunung Jati Ba'alawy Semarang with a total population of 79, so the sampling used saturated samples because it was less than 100. The data collection method used a questionnaire that was tested for validity and reliability. The results of this study determined the influence of the variable role of teachers, principal leadership, and school discipline on student discipline.